2022
DOI: 10.1007/s00259-022-05951-1
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Hetero-bivalent agents targeting FAP and PSMA

Abstract: This article is part of the Topical Collection on Erratum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A recent proteomic study on PCa para n-embedded (FFPE) tissue samples showed that protein VCAN is associated with biochemical recurrence of PCa, could be a prognostic marker (Lygirou et al 2022). another study con rmed that FAP has potential as a diagnostic and therapeutic target, and PCa tissue could be better visualized in positron emission tomography/computed tomography (PET/CT) using a developer targeting FAP (Boinapally et al 2022). In addition, previous in vitro studies con rmed that 1upregulating SFRP in PCa cell lines could induced epithelial-mesenchymal transformation (EMT), transform PCa cells into osteoblast-like phenotypes that conducive to survival in bone metastases (Kato et al 2019).…”
Section: Discussionmentioning
confidence: 97%
“…A recent proteomic study on PCa para n-embedded (FFPE) tissue samples showed that protein VCAN is associated with biochemical recurrence of PCa, could be a prognostic marker (Lygirou et al 2022). another study con rmed that FAP has potential as a diagnostic and therapeutic target, and PCa tissue could be better visualized in positron emission tomography/computed tomography (PET/CT) using a developer targeting FAP (Boinapally et al 2022). In addition, previous in vitro studies con rmed that 1upregulating SFRP in PCa cell lines could induced epithelial-mesenchymal transformation (EMT), transform PCa cells into osteoblast-like phenotypes that conducive to survival in bone metastases (Kato et al 2019).…”
Section: Discussionmentioning
confidence: 97%
“…Polymeric peptides constructed on the basis of the polyvalent effect can improve the tumor-targeting ability and prolong tumor retention time remarkably. Plenty of polymerized peptides have been reported previously, and polymerization can be performed between the same peptides, such as 2P(RGD) 2 [33] and 2P(FAPI) [24], or between two kinds of peptides, for example, PSMA-FAPI [34] and RGD-FAPI [35]. According to current clinical data, based on polymerization strategy, 2P(RGD) 2 and 2P(FAPI) have been constructed and testified to gain an increased tumor uptake rate and better tumor retention capacity.…”
Section: Discussionmentioning
confidence: 99%